Asia- Europe : The third link - Cohen- Setton, Jeremie; Pisani-Ferry, Jean.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : Office for Infrastructures and Logistics in Brussels, 2008)
This paper provides an overview of the relative weight of Europe and East Asia in the context of the world economy and it assesses interdependence between the two regions. The prime motivation of the paper is that linkages between Europe and East Asia remain frequently underestimated. While the "third link" between them is in many respects as important as the linkages between the two regions and North America, it is too often regarded only as of secondary importance.
Economic Papers.